2005
DOI: 10.1302/0301-620x.87b5.15542
|View full text |Cite
|
Sign up to set email alerts
|

Repair of large full-thickness articular cartilage defects in the rabbit

Abstract: We produced large full-thickness articular cartilage defects in 33 rabbits in order to evaluate the effect of joint distraction and autologous culture-expanded bone-marrow-derived mesenchymal cell transplantation (ACBMT) at 12 weeks. After fixing the knee on a hinged external fixator, we resected the entire surface of the tibial plateau. We studied three groups: 1) with and without joint distraction; 2) with joint distraction and collagen gel, and 3) with joint distraction and ACBMT and collagen gel. The histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(19 citation statements)
references
References 40 publications
(45 reference statements)
0
18
1
Order By: Relevance
“…It was our initial assumption that although the increase in cartilage thickness has to correlate with the increase in animal size e.g. goat cartilage is thicker than rats; it is unlikely that cell density will differ when we consider that the size of chondrocyte of any mammal should remain similar, especially in quadrupeds [15,18]. The present study also showed that weight and size of the animals play a significant role in maintaining cartilage thickness, a fact that is supported by several published literatures [19-21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was our initial assumption that although the increase in cartilage thickness has to correlate with the increase in animal size e.g. goat cartilage is thicker than rats; it is unlikely that cell density will differ when we consider that the size of chondrocyte of any mammal should remain similar, especially in quadrupeds [15,18]. The present study also showed that weight and size of the animals play a significant role in maintaining cartilage thickness, a fact that is supported by several published literatures [19-21].…”
Section: Discussionmentioning
confidence: 99%
“…It is reasonable to assume that the increase in cell numbers would correlate proportionately to the increase cartilage thickness. It is worth noting that in previous studies, it appears that the differences in cartilage thickness between animals has no direct correlation with their cell densities and that cell density is more likely to be species specific [15]. However, considering that cartilage of any animal would have similar functions regardless of its size, there should not be apparent discrepancies in the GAGs/protein/cell and selected cartilage genes.…”
Section: Introductionmentioning
confidence: 99%
“…MSCs are said to have extensive self-renewal, long-term cell viability and multi-lineage potential together with a lack of or minimal immunogenicity (Lin et al 2005). Adult stem cells derived from a myriad of sources (bone marrow, fat pad, synovial fluid, dental pulp and periosteum) have demonstrated chondrogenic potential in vitro (Emans et al 2005; Estes et al 2006; Johnstone et al 1998; Shintani and Hunziker 2007; Yanai et al 2005). Some of these stem cells have been used clinically to regenerate bone but their clinical application in regenerating human cartilage is either undocumented or in the early stages (Horwitz et al 2002; Wakitani et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…However, different protocols are used by different research groups, making it a challenge to compare between different studies; thus, the optimum cell source and culture conditions for use in cartilage tissue repair is yet to be determined (Chen and Tuan 2008). To date, human bone marrow MSCs (HBMSCs) remain the most studied and best understood stem cell source used in cartilage tissue engineering (Chen et al 2005; Johnstone et al 1998; Mackay et al 1998; Penick et al 2005; Ponticiello et al 2000; Wayne et al 2005; Yanai et al 2005)…”
Section: Introductionmentioning
confidence: 99%
“…[4][5] Cartilage defects are most commonly seen in the knee joint mostly due to trauma.6 Many cartilage repair procedures are introduced as open surgical procedures (osteotomy and distraction of joints), cartilage transplantation, tissue engineering, autologous chondrocyte implantation, autologous condition plasma, pridie drilling and microfracture, perichondral and periosteal grafts, fetal membranes, and intra-articular hyaluronan injection. [5][6][7][8][9][10][11][12][13][14][15][16] There are several methods of fixation of autologous cartilage graft including polydioxanone pins, krishner wires, Herbert screws, cyanoacrylate adhesive, polymethylmethacrylate cement, stainless steel nails, and suture. [17][18][19] The aim of this study was to evaluate the healing effect of bioglue in experimentally-induced femoral condyle articular cartilage defect in rabbit as an animal model.…”
Section: Introductionmentioning
confidence: 99%